Dampak TIK terhadap Produktivitas Tenaga Kerja dalam Mencapai Visi Indonesia Emas 2045 - Maharani, Rafaela Suryadiva Indira; Kartiasih, Fitri; Amalia Isti Widiyasari (Ekonomi dan Bisnis, 2025)
Purpose: This research aims to analyse the variables that influence labour productivity in Indonesia, with a focus on the role of information and communication technology (ICT) in supporting inclusive and sustainable economic growth towards the Vision of Golden Indonesia 2045. Design/methodology/approach: This study uses panel data from 34 provinces over the period 2015–2022. The estimation model used is Feasible Generalised Least Squares (FGLS). The variables analysed include physical capital, human capital, trade openness, real wages, mobile phone ownership, and internet access. Findings: The results show that physical capital, human capital, trade openness, real wages, and internet access have a significantly positive impact on labour productivity. On the contrary, mobile phone ownership has a significant negative impact, indicating that the utilisation of ICT for productivity is still not optimal. Research limitations/implications: The research is limited to provincial-level data and quantitative ICT indicators, thus it has not captured the aspects of quality and user behaviour. Further studies can explore the interactions between variables and the long-term effects of ICT utilisation. Practical implications: The government needs to promote the equitable distribution of internet infrastructure, enhance digital literacy, and implement policies that can reduce the disruptive impact of ICT on workers, in order to optimise the potential of digitalisation inclusively. Originality/value: This research offers a new contribution by using provincial panel data from 2015–2022 and analysing the differences in the impact of ICT between the western and eastern regions of Indonesia, as well as explicitly integrating ICT indicators into the analysis model. Paper type: Research paper.   Keywords: Output Gap, NTB, Potential RGDP, R-Statistics.